Dynamic simulation tools for main metabolic pathway of escherichia coli - Hazwan Arif, Mazlan (2013)
Metabolic engineering is the study of metabolic pathways modification in one organism by increasing the metabolite production through genetic engineering in order to bring the new and better product in food, feed, pharmaceuticals and many more. The studies of metabolic pathway give opportunity to scientists to discover a new phenomenon in cells and proposed many mathematical models for each of the cells behavior. Most of the cells used in experiments are Escherichia coli (E. coli). However, conducting experiments of E. coli are time and money consuming and scientists found it the existing dynamic simulators are complex in order to simulate the proposed mathematical model and some of them prefer to do hardcode simulation. These problems give opportunity to computer scientist to develop the dynamic simulation tools for main metabolic pathway of E. coli that are simpler than the existing tools. The development tools used for the project are Visual Studio 2010. The dynamic simulation tools contain of 2 main modules – Metabolites configurations and Graph configurations. User needs to undergo four ( 4 ) tab pages in Metabolites Configurations module and two ( 2 ) tab pages in Graph Configurations. The technique used in this project is Ordinary Differential Equations ( ODE ) of Runge-Kutta.